A cyclic integrated microstructural-mechanical model for a shape memory alloy. (December 2021) - Bellini, C.; Berto, F.; Di Cocco, V.; Iacoviello, F.
Highlights: A structural-mechanical model is proposed to describe the cyclic behaviour of SMA. A microstructural model is used to evaluate the level of phase transformation. Model parameters depend on loading conditions and number of cycles. Alloy stiffness in the plateau depends on those of the constituent phases. Abstract: Shape memory alloys are able to recover the initial shape even after a large deformation. The memory property is due to the ability to change the microstructure under a variation of the stress state or the temperature. The stress–strain curve is characterized by the presence of a stage where the slope of the curve sharply decreases and the initial microstructure transforms into a new one. In this work, an integrated microstructural-mechanical model is proposed for the equiatomic NiTi shape memory alloy, that is suitable to predict the cyclic behaviour of a pseudoelastic shape memory alloy starting from the microstructure composition.